A new species of Collybiopsis (Omphalotaceae, Agaricales) from India - Ratheesh, S.; Kumar, A. Manoj; Pradeep, C.k. (Phytotaxa, 2026)
A novel species of Collybiopsis was discovered during an investigation on the diversity of agaricoid fungi in Kerala State, India. The identification and characterization of this taxon were carried out through detailed morphological examinations, coupled with a two-locus phylogenetic analysis. A combined dataset of nucleotide sequences from the internal transcribed spacer (nrITS) and the large subunit (nLSU) regions confirmed the distinct phylogenetic placement of the species within the genus Collybiopsis. Herein, we provide a comprehensive description, detailed illustrations, and phylogenetic analysis results of C. brunneigalera, highlighting its unique diagnostic features and phylogenetic affinities.